An Analysis of Digital Marketing Strategies and Website Content Usage : Key Requirements, Metrics and Tactics for Hyper-Personalized SMEs Websites - Julia N. Korongo,; Dr. Anselemo P. Ikoha,; Dr. Alice W. Nambiro, (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The study evaluates the integration of website content into Digital Marketing Strategies (DMS) to drive the hyper-personalization of Small and Medium Enterprises (SMEs) websites. The study's objectives were to analyse the key requirements and metrics for integrating website content and DMS for SMEs websites, examine the relationship between website content consumption patterns and DMS, and suggest data-driven tactics for hyper-personalized SMEs websites. The study employs a descriptive design and targets a sample of 95 Digital Marketing Agencies using random and purposive sampling techniques. Data collection was through an online questionnaire and desktop research. Data analysis was done through content analysis and the IBM SPSS statistical tool for descriptive and inferential statistics. The Spearman’s rank correlation revealed patterns highlighting both positive and negative monotonic associations between website content usage and DMS. Additionally, the results show that digital marketing strategies have a statistically significant impact on content usage that can influence the hyper-personalization of websites. In today’s competitive landscape, hyper-personalized websites are essential for SMEs to stand out. Therefore, the study suggests data-driven tactics for leveraging hyper-personalized websites to gain a competitive edge in the digital era.
Keywords: Digital Marketing Agencies; Digital Marketing Strategies; Hyper-personalization; SMEs Websites; Website Content